FROM DISCIPLINE TO DEVELOPMENT: ADAPTING CORE MARCHING BAND STRUCTURES FOR DEVELOPMENTALLY APPROPRIATE PRACTICE IN INDONESIAN EARLY CHILDHOOD EDUCATION - Iwan Kurniawan; Joko Pamungkas (PT. Jurnal Center Indonesia Publisher, 2026)
This study examines how core marching band structures can be adapted for Indonesian early childhood education through developmentally appropriate practice and performance theory. The study responds to concerns that preschool marching band activities may reproduce discipline-oriented rehearsal models designed for older learners. A one-group pre-test and post-test mixed-methods design was used with twenty Indonesian preschool children aged four to five years. Over six weeks, children participated in twelve adapted marching band sessions that combined simplified rhythmic patterns, child-scaled instruments, neat but developmentally adjusted formations, cooperative music-making, visual-motor activities, and responsive teacher facilitation. Quantitative data were collected using a four-point developmental observation rubric covering rhythmic competence, motor coordination, and socio-emotional engagement. Qualitative data were obtained from teacher reflective journals and post-intervention interviews. Paired-sample analysis showed higher post-test scores across the three developmental domains. The largest observed improvement appeared in socio-emotional engagement, followed by rhythmic competence and motor coordination. However, because the study did not include a control group, the findings should be interpreted as developmental changes observed after participation rather than definitive causal effects of the intervention. Qualitative findings indicated that children participated more confidently when teachers simplified rhythmic tasks, used clear and neat formations with reduced technical pressure, provided child-scaled instruments, supported safe movement, and acted as co-players and emotional co-regulators. The study reconceptualizes marching band routines not as rigid disciplinary scripts, but as adaptable performative frames that may support social participation, emotional regulation, rhythmic learning, motor coordination, cooperation, and creative agency when aligned with children’s developmental readiness.